A Promising Catalytic and Theranostic Agent Obtained through the In‐Situ Synthesis of Au Nanoparticles with a Reduced Polyoxometalate Incorporated within Mesoporous MIL‐101. Issue 27 (27th June 2016) - Roch‐Marchal, Catherine; Hidalgo, Tania; Banh, Hung; Fischer, Roland A.; Horcajada, Patricia
Abstract : A well‐controlled three‐step green synthetic method allows the synthesis of composite materials based on the highly stable chromium(III) terephthalate MIL‐101(Cr) with gold nanoparticles (NPs) and polyoxometalates (POMs) inside its mesopores. First, the POM was included within the MIL‐101(Cr) cavities through the direct synthesis of MIL‐101(Cr) in the presence of the preformed H3 PMo12 O40 POM. Then, the incorporated POM was reduced in situ with H2 . Finally, an in‐situ soft reduction of HAuCl4 by the reduced POM led to the formation of Au NPs and oxidized POM within the MIL‐101(Cr) structure [(Au)H2red POM@101]. A final Au/POM atomic ratio of 1.8 was reached. The chemical and structural stabilities of both MIL‐101(Cr) and the POM were preserved during the whole process. In addition to the potential catalytic properties of these highly porous composite systems, we have demonstrated their promising performance as optical contrast agents. The (Au)H2red POM@101 composites exhibited excellent biostability and were rapidly internalized in macrophage cells, as observed through fluorescence confocal microscopy. Abstract : Promising catalysts and optical contrast agents based on (Au)POM@MOF (POM = polyoxometalate, MOF = metal–organic framework) composites are synthesized in situ through the incorporation of a POM into the mesopores of MIL‐101, followed by reduction to form Au nanoparticles. These composites are internalized rapidly by cells, and no Au/POM leaching or MOF biodegradation occurs.